Placebos as a Source of Agency: Evidence and Implications - Friesen, Phoebe (Frontiers in Psychiatry, 2019)
Bioethical discussions surrounding the use of placebos in clinical practice have long revolved around the moral permissibility of deceiving a patient if it is likely to benefit them. While these discussions have been insightful and productive, they reinforce the notion that placebo effects can only be induced through deception. This paper challenges this notion, looking beyond the paradigmatic clinical encounter involving deceptive placebos and towards many other routes that bring about placebo effects. After briefly describing the bioethical terrain surrounding the deceptive use of placebos in clinical practice, section 1 offers an examination of the various mechanisms known to contribute to placebo effects: classical conditioning, expectations, affective pathways, open-label placebo treatments, and additional factors that do not fall easily into a single category. The following section explores how each of these routes can be harnessed to bring about clinical benefits without the use of deception. This provides grounding for reconceiving of the placebo effect as a clinical tool that is not always in conflict with patient autonomy and can even be seen as a source of agency. In the final section, implications of the shift away from seeing placebos as necessarily deceptive are discussed. These include the necessity of looking beyond the clinical encounter and mainstream medicine as the primary sites of placebo responses, how important acknowledging the limits of placebo effects will be when we do so, as well as the difficulties of disentangling agency, responsibility, and blame within medicine.